BERBEDAKAH MOTIVASI BERAGAMA KELOMPOK AKSI BELA ISLAM 212 DENGAN KELOMPOK NON AKSI BELA ISLAM 212? - Gessike Putri Ramadani; Yulmaida Amir; Ilham Mundzir (Prosiding Seminar Nasional Berseri, 2020)
This study aims to determine whether the 212 Islamic Defenders Action group has different religious motivations from non-Islamic Defendance Action groups 212. Religious motivation in this case is seen from the religious orientation and internalization of Religion. The religious orientation in question is the tendency regarding the origin of the motives that underlie one's religious behavior. In this case, whether intrinsically oriented (based on religion and the teachings of the religion), or extrinsic oriented (based on individual personal motives, religion as a means to an end). The measuring instrument used is the Religioius Orientation Scale (ROS). Internalization of religion is about the extent to which religious teachings are adopted by individuals as a part of themselves. Measuring instruments use the scale of Religious Internalization. The subjects in this study were 100 people. 50 people from the Islamic Defenders Action group 212 and 50 non-Islamic Defenders Action groups. The results showed that there were differences in religious orientation in the non-Islamic Action Group 212 (p =, 001 <, 05), namely the non-Islamic Action Group 212 non-intrinsically oriented group, while the Islamic Defensive Action group 212 there was no difference between the intricate orientation and extrinsic. The results of the Internalisation of Religion measurement show that in general the internalization or adoption of religion is more seen in the non-Islamic Defendant Action group 212 than the Islamic Defendant Action 212. However, when viewed further from the type of religious internalization the difference is also seen namely: the Islamic Defendant Action Group 212 tends to be more independent in making the value of Religion a part of him. While there is no difference between the level of independence in the Islamic Action Group and the influence of external factors in the process of adopting religious values.